Persistently luminescent materials : from development to applications - Mao, Yuanbing (Wiley-VCH, 2025)
A broad view of the booming field in optical materials based on their applications and potentials. Persistent luminescence refers to a property of materials in which they retain luminescence for hours or even days without a source of excitation once being charged. Persistently luminescent materials have found a huge range of technological applications, from optical displays to chemical sensing to information storage and security technologies. This growing field of research and development has never been such an important area of materials science. Persistently Luminescent Materials offers a comprehensive overview of these emerging optical materials and their applications. It presents all major research trends, new information, and novel properties of the major and developing persistently luminescent materials. With detailed information on how to design new materials and create new functionalities, it's a must for researchers and technologists in virtually every major area of industry. Persistently Luminescent Materials readers will also find: - Practical applications in phototherapy, biological imaging, displays, and more - Detailed discussion of topics including sustainability techniques, temperature sensing, sterilization, and optical information storage - Analysis of how to use persistently luminescent materials to create new theranostic functionalities Persistently Luminescent Materials is ideal for specialists and professionals in the field, but also for a broader readership seeking a perspective of practical needs related to the applications of optical and perticularly persistently luminescent materials.
Keywords: Luminescence.; elektronické knihy; electronic books